Cultural intelligence model based on value “pintar tuntang harati” for growing peace in senior high school students in Palangka Raya City - Fendahapsari Singgih Sendayu; Sunaryo Alidha Sunaryo (Universitas Muhammadiyah Ponorogo, 2020)
Cultural intelligence is built on the ability of self to cultivate awareness in accommodating cultural experiences encountered in everyday life as a counterweight of cognitive intelligence that can be applied in certain attitudes in everyday life. Cultural intelligence occurs when there is interaction among a group of individuals, both social interaction and cultural interaction. Implementation of local cultural values in the development of the educational process becomes very important in an effort to strengthen the character of the nation. The value of the culture of local wisdom about